Job Discipline, Competency, Environmental Instability, and Work Effectiveness in Gorontalo Province on Employee Quality in Tourism Industry - RAHMAN, Yurni; ISHAK, Irmawati D.; HARIS, Ikhfan; ALDI, B. Elnath; YUNIAWATI, Ayi Srie (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021, 2021)
The purpose of this study was to explore the influence of work discipline, competency, environmental instability, and work effectiveness on employee Quality in the tourism industry in Gorontalo Province. The number of samples was 283. Data were collected using the nonprobability sampling and accidental sampling and were analyzed using the quantitative descriptive analysis. Based on the SPSS analysis, work discipline had a significant influence on employee Quality in the tourism industry in Gorontalo Province. The competency had a significant influence on employee Quality in the tourism industry in Gorontalo Province. The environmental instability had a significant influence on employee Quality in the tourism industry in Gorontalo Province. The work effectiveness had a significant influence on employee Quality in the tourism industry in Gorontalo Province. The work discipline, competency, environmental instability, and work effectiveness variables simultaneously had a significant influence on employee Quality in the tourism industry in Gorontalo Province